Morphology of polyethylene ski base materials - Fischer, J.; Wallner, G. M.; Pieber, A. (Journal of Sports Sciences, 2010)
We used high-resolution Raman spectroscopy and differential scanning calorimetry for a comprehensive analysis of carbon black-filled polyethylene ski base grades at processing stages from the raw material to the structured ski base. Based on Raman mapping, we assessed the applicability of an advanced evaluation procedure for amorphous, disordered, and crystalline phase fractions of polyethylene for polyethylene extrusion and sinter grades. For sinter grades, a sufficient segregation between carbon black and polyethylene was confirmed, allowing for a comprehensive Raman spectroscopic morphological analysis. Significant morphological changes in polyethylene due to processing from the raw material to the semi-finished film and to the structured ski base were identified. Throughout the processing chain, we observed a decrease in crystallinity and an increase in the amorphous phase fraction. Although the raw material and the sintered semi-finished film exhibited a different but uniform polyethylene morphology, the morphological changes due to structuring of the ski base are limited to the top surface layer. The highest amorphous phase fractions were detected in the surface of the structured ski bases.